Pollution indices as tools for evaluation of the accumulation and military activities on the molotov line during WWII still detectable in the chemical record of soils in Roztocze (SE Poland) - Plak, Andrzej; Gajek, Grzegorz; Telecka, Małgorzata; Hałas, Paulina; Bis, Małgorzata; Szafran, Tomasz (Quaestiones Geographicae, 2025)
This paper aimed to investigate the extent of trace metal (TM) contamination of soils in areas adjacent to the bunkers of the Molotov Line in Poland and to assess reclamation activities on the extent of TM contamination of soils. The Molotov Line is a zone of Soviet fortifications constructed in 1940–41. Surface (0–20 cm) and subsurface (20–40 cm) soil samples were collected at four transects and distances from the bunkers. TMs (Cd, Cu, Mn, Pb, Zn, Ni, Cr and Bi), pH, texture, TOC, HA, base exchange capacity (BEC) and effective cation exchange capacity (ECEC) were determined in the investigated soils. Several indicators of contamination were used to analyse the degree of contamination: Igeo, pollution load index (PLI), pollution index (PI), CD, RI and top-bottom (TB) index. The conducted research has revealed that soils subjected to military pressure exhibit different properties from natural soils. The TM content in the 0–20 cm soil layers was higher than in the subsurface layers and several times higher than the geochemical background. This indicates that despite remediation efforts (ploughing and afforestation), there exists a clear geochemical record of military activities along the Molotov Line. Thanks to the contamination indices used in this study, it was found that soils affected by the past wartime activities may pose a real threat to health. The regularities presented in this study can provide a basis for action regarding the direction of remediation activities for areas with sensitive uses, such as military training grounds. The results presented here allow us to conclude that despite the remediation activities undertaken, there is a clear geochemical record of military activities on the Molotov Line.